Transformed management scholarship and ways forward for exploring social innovation in organizations - Taylor, Rachel; Torugsa, Nuttaneeya (Ann); Arundel, Anthony (International Studies of Management & Organization, 2020)
Inspired by recent calls for a transformation of management scholarship, we conduct a scoping review of empirical studies during 1998–2015 on the phenomenon of social innovation within organizations. Social innovations are novel solutions that address social problems and create value for society as a whole. We make several problem-based observations and suggest how the social innovation phenomenon can be empirically grounded and contextualized to make future research intellectually relevant and meaningful for practice. We propose that the way forward lies in using abduction as a logic of discovery, adopting complexity theorizing, and using set-theoretic analytical methods to reflect multiple realities. The application of these three methods will help link theory and research methods with practice, thereby improving the ability of research to tackle managerial and societal issues and hence strengthening management scholarship.
Number: 2
Keywords: management scholarship